Dose of intra‐operative opioids has no impact on recurrence or survival in primary liver cancer - Liuyuan Zhao; Lei Teng; Wenhui Zhang; Shiyan Lin; Xuejiao Liu; Junzhu Dai; Hongxue Shao; Xiaoshi Li; Quan Liu; Huichao Zou (Cancer Medicine, 2022)
Abstract Background Intra‐operative use of opioid analgesics might have an impact on cancer recurrence and survival after surgery. The objective of this study was to investigate the association between the intra‐operative fentanyl equivalents and survival outcomes in patients with primary liver cancer after receiving hepatectomy. Methods This was a retrospective single‐center cohort study, and clinical data of 700 patients with primary liver cancer who underwent hepatectomy in Harbin Medical University Cancer Hospital from September 2013 to August 2018 were reviewed. After propensity matching, 376 patients were included. Patients were divided into high‐dose and low‐dose groups according to the median intra‐operative fentanyl equivalents (1.500 mg). Kaplan Meier curve and Cox proportional hazards regression model were used. Results Results of univariable analysis showed there were no significant differences in recurrence‐free survival (RFS) (p = 0.136) and overall survival (OS) (p = 0.444) between high‐dose fentanyl equivalents and low‐dose fentanyl equivalents group. The multivariable Cox regression analysis found that the dose of intra‐operative fentanyl equivalents was not associated with RFS (HR: 1.119, 95%CI: 0.851–1.472, p = 0.422) or OS (HR: 0.939, 95%CI: 0.668–1.319, p = 0.715). Conclusions The amounts of intra‐operative fentanyl equivalents had no impact on recurrence‐free or overall survival in patients with primary liver cancer after curative hepatectomy.